The sayings in the Peruvian Traditions by Ricardo Palma - Huárag Álvarez, Eduardo (2019)
This article discusses the importance of proverbs and sayings in the Peruvian Traditions. Being a type of communication, a tradition, a type of language usage and a way to express understanding of realities or social occurring, proverbs are rooted in the Ibero-American culture. They have always existed, although in the romantic period they become particularly important due to the interest of the romantics in popular folklore. Through the analysis of several traditions by Palma, we can demonstrate the importance of proverbs and the way they are inserted into a story such as Peruvian Traditions.